Would entitled people be more proactive at work? Examining contrasting mechanisms based on the proactive motivation model - Shipan Yang; Cheng Quan; Zijun Cai (Acta Psychologica)
Previous research has largely regarded psychological entitlement as detrimental to organizational effectiveness. In contrast, this study presents a more nuanced view by exploring its relationship with proactive work behavior. Drawing on the proactive motivation model, we propose that psychological entitlement influences proactive work behavior in both positive and negative ways, with need for uniqueness, role-breadth self-efficacy, and emotional exhaustion serving as mediators for the “reason to,” “can do,” and “energized to” states, respectively. Through a field study and an experiment, our results consistently showed that psychological entitlement had positive influences on proactive work behavior. Our study thus highlights that psychological entitlement should not be seen solely as problematic, sheds light on new mechanisms through which it influences work outcomes, and deepens our understanding of individual differences in proactive behavior at work.